REINFORCING ISLAMIC MORAL VALUES THROUGH CONTEMPORARY PESANTREN EDUCATION : A PATHWAY TO CHARACTER DEVELOPMENT - Sarwadi, Sarwadi; Raihan, Nur (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to explore how contemporary Pesantren education reinforces Islamic moral values and contributes to character development among students. It investigates the methods and strategies employed by Pesantren in instilling moral principles such as integrity, social responsibility, and spiritual growth. Method: Through a qualitative case study approach, the research investigates how pesantren education fosters character development aligned with Islamic ethics. Result: The findings reveal that pesantren integrate religious teachings, daily routines, and role modeling as key mechanisms in shaping students’ moral behavior. Moreover, institutional culture, teacher consistency, and community involvement significantly influence the success of moral education. Conclusion: This study contributes to a deeper understanding of Islamic character education within the pesantren system and offers strategic insights for Islamic educational institutions in enhancing value-based education.